ROBERT BRUCE SPENCER AND HIS IDEOLOGY ON ISLAM AND COMPILING QUR’AN - Taswar Hussain; Hafiz Muhammad Iftikhar Ahmad (دی اسکالر)
Robert Spencer is one of the American blogger orientalist of present time, writer of the thirty books almost never let any chance to defame Islam and Quran. He is the person who often addresses the agencies and other law enforcement agencies’ to set their goals and direction regarding the policies of third world countries and he excessively utilized electronic media. He debates on Fox news about Islam and jihad and talk on terrorism. He had the eyes of eagle on any incident where ever happen to put its responsibility over the Muslims. As everybody knows after the incident of 9/11 Quran was sharply recited in Europe and America and a lot of people accept Islam who judged honestly that it is not the religion of terrorism. Then he thought it is the apt time to create some doubts in Quran. He confesses in his book that Islam and Quran were widely studied by the Americans. Being he member of the organization stop Islamization in America he wrote much against Islam and about compiling Quran.